Halal Tourism Industry in Indonesia: Potential and Prospects - Jaelani, Aan (International Review of Management and Marketing, 2017)
This study confirms that halal tourism is a tourism industry which has contributed to economic growth in Indonesia, although the world economy slows down. In Indonesia, halal tourism has long been grown in the form of a pilgrimage undertaken by people with religious motivation. Along with the development of the global Islamic economy, then this type of tourism is undergoing a metamorphosis that requires a change in modern ranging from attractions, hotels, up to marketing.The paper combines descriptive of halal tourism industry and practices of Islamic law in Indonesia. This approach found that halal tourism industry can not be separated from the religious practices of the majority of Muslims in Indonesia, but also economically contribute to the local community, and tourist sites that display the beauty and hospitality for tourists Muslims and non-Muslims. This study concludes that halal tourism has become part of the national tourism industry to position Indonesia as a center for halal tourism in the world in the future. Keywords: industry, religion tourism, shariah tourism, halal tourism JEL Classifications: L83, N53, Q57, Z31, Z32